(untitled) (Environment & Health, 2024)
Population studies often require assessing the mental state of children and adolescents. The Revised Children’s Anxiety and Depression Scale (RCADS-P-25) is an internationally recognized tool used to measure anxiety and depression levels in 8 to 18-years-old children and adolescents. This study aimed to evaluate the validity and reliability of the shortened version of the RCADS-P-25, completed by parents or guardians, for the Ukrainian population. Materials and methods: The RCADS-25 tool was translated into Ukrainian and adapted for cultural relevance. Validity was assessed through factor analysis, and reliability was evaluated using Cronbach’s alpha and test-retest analysis. The pilot study involved 763 parents, and 5,695 RCADS-P-25 scales were analyzed from 2020 to 2024. Results: Factor analysis confirmed a two-factor structure consistent with the original version of the RCADS-P-25. The internal consistency was high, with Cronbach’s alpha coefficients ranging from 0.83 to 0.92 in 2020. The average Cronbach’s alpha from 2020 to 2024 was 0.88 (0.87-0.88; F=8.1; p